Evaluation of the Clinical and Laboratory Status of Pregnant Women with COVID-19 - Rashidi Fakari, Farzaneh; Pordel, Sana; Armide, Kimiya; Azimian, Amir; Taghavi, Mohammad Reza; Farrokhi, Esmaeil (Advances in Nursing & Midwifery, 2022)
Abstract Introduction: The prevalence of the COVID-19 virus has been very high, so that in a short period of time, due to its contagiousness, it has infected a large number of people around the world. Pregnant women are more sensitive to infectious diseases than the general population and are especially at risk of respiratory diseases and severe pneumonia. Considering the importance of mother and fetus management, assessment and management of pregnant women infected with COVID-19, the present study was conducted with the aim of investigating the clinical and laboratory status of pregnant women infected with SARS‐CoV‐2 referring to Imam Hassan and Bentolhoda hospital in Bojnurd. Methods: In this cross-sectional study, pregnant women with COVID-19 referred to Imam Hassan and Bentolhoda Hospital in Bojnurd between March 2020 and the beginning of Desember 2021 were studied. In order to collect information, an information form containing demographic and obstetric characteristics, evaluation of symptoms (fever, cough, abdominal pain, bloody secretions, rupture of fetal membranes in term pregnancy, chest tightness, asthma, fatigue, loss of appetite, headache, nausea and vomiting), laboratory status and outcomes pregnancy and childbirth was used. Statistical analysis was done with SPSS 24 software. Results: The age range of the studied women was 15-48 years and the average gestational age was 26.21±9.4 weeks. The type of delivery in 46.2% was normal vaginal delivery, 53.8% was cesarean section. LBW, admission to NICU, need for resuscitation, meconium-stained AF were 5.71%, 4.76%, 3.80%, 0.95%, respectively. The average number of referrals to the hospital due to COVID-19 in the studied women was 1.6 ± 1.1 times, the average number of days in the hospital was 5.1 ± 3.1 days, and the average number of days in the intensive care unit was 4.08±2.1 days. The most common clinical symptoms in the studied women were related to cough (76.19), dyspnea (72.38), fever (56.19), and myalgia (33.33). Conclusions: Based on the results obtained from this study, clinical symptoms and laboratory results in pregnant women with COVID-19 are similar to infected adults. Common symptoms of COVID-19 disease in pregnant women included fever, cough, and myalgia.